Revealing Heleieth Saffioti - Motta, Daniele Cordeiro (Pontifícia Universidade Católica de São Paulo, 2019)
This article attempts to contextualize the author’s formulations on the “node” of gender, race/ethnicity and class, which is the articulation of what the author considers the three founding conditions of our society. We understand that Saffioti’s contribution is a Brazilian perspective on the theory of the articulation between gender, race and class. In this way, we situate the author in the field of studies on intersectionality, highlighting the importance of her contribution to the analysis of the relationship between the different aspects of Brazilian social diversity and class inequality. To that end, we discuss the importance of the category of patriarchy for Heleieth Saffioti’s analysis, pointing to the possibility of dialogues between the feminist conception and its use in the tradition of Brazilian thought.